2021
DOI: 10.3390/insects12050420
|View full text |Cite
|
Sign up to set email alerts
|

Mild Abiotic Stress Affects Development and Stimulates Hormesis of Hemp Aphid Phorodon cannabis

Abstract: The hemp aphid Phorodon cannabis Passerini is a well- known (Asia, Europe) or newly emerging (North America) insect. It is a monophagous insect pest causing considerable damage in field and glasshouse cultivations. The aim of this work was to study the effects of meteorological (temperature) and agronomical (herbicide) factors on the biology of the hemp aphid. In one experiment, hemp plants were kept at constant temperatures ranging from 20 to 30 °C, and aphid survival and fecundity were measured. In a related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Temperature is one factor widely discussed as affecting longevity and it can determine the lifespan of many model organisms, for example, fungi Saccharomyces cerevisiae [ 55 ], Caenorhabditis elegans [ 56 ] or Drosophila melanogaster [ 32 ]. For aphids, it has also been noted that there is a negative correlation between temperature and longevity [ 57 , 58 , 59 ], but in some aphids, the opposite effect was observed in relation to the optimum temperature of the species [ 60 ]. Our research confirmed that metabolic rate is an important determinant of longevity, thus indicating that an increase in ambient temperature will increase enzyme activity and shorten aphid longevity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature is one factor widely discussed as affecting longevity and it can determine the lifespan of many model organisms, for example, fungi Saccharomyces cerevisiae [ 55 ], Caenorhabditis elegans [ 56 ] or Drosophila melanogaster [ 32 ]. For aphids, it has also been noted that there is a negative correlation between temperature and longevity [ 57 , 58 , 59 ], but in some aphids, the opposite effect was observed in relation to the optimum temperature of the species [ 60 ]. Our research confirmed that metabolic rate is an important determinant of longevity, thus indicating that an increase in ambient temperature will increase enzyme activity and shorten aphid longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Our results strongly correspond to the data obtained for the English grain aphid Sitobion avenae , which showed that the basal thermal tolerance of this species varied during development and was highest in the 3rd and 4th nymphs [ 61 ]. Changes in basal tolerance at the adult stage might result from a trade-off between heat tolerance and reproductive output, but may also result from behavioural thermoregulation abilities present in adult aphids [ 59 ]. Probably because the behavioural mechanisms of nymphs function poorly, we observed the need for high antioxidant activity of enzymes to effectively enable the protection of nymphs and allow them to continue development to maturity.…”
Section: Discussionmentioning
confidence: 99%
“…The cannabis aphid ( Phorodon cannabis Passerini) is a pest and monophagous herbivore of Cannabis spp. ( Cranshaw et al 2018 , Durak et al 2021 ). The aphid feeds by piercing the plant with its mouthparts and tapping directly into the phloem, ingesting the sugary sap produced through photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The aphid feeds by piercing the plant with its mouthparts and tapping directly into the phloem, ingesting the sugary sap produced through photosynthesis. Aphid herbivory can adversely affect the fitness and yield of Cannabis plants through direct damage and the transmission of plant viruses and is exacerbated by their capacity for rapid population growth ( McPartland et al 2000 , Durak et al 2021 , Pitt et al 2022 ). Their high reproductive potential, in addition to their ability to transmit viruses, contributes to their pest status.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most important arthropod pests of indoor medical Cannabis cultivation include: cannabis aphid (Phorodon cannabis Passerini), rice root aphid (Rhopalosiphum abdominalis Sasaki), cotton/melon aphid (Aphis gossypii Glover), sweetpotato whitefly (Bemisia tabaci Gennadius), onion thrips (Thrips tabaci Lindeman), western flower thrips (Frankliniella occidentalis Pergande), twospotted spider mite (Tetranychus urticae Koch) and hemp russet mite (Aculops cannibicola Farkas). 18,23 Other arthropod pests of increasing consideration for outdoor medical Cannabis production include: Japanese beetle (Popillia japonica Newman), grasshoppers, brown marmorated stink bug (Halyomorpha halys Stål), Eurasian hemp moth (Grapholita delineana Walker) and corn earworm (Helicoverpa zea Boddie). 17,18,24 Pest management techniques are key in maintaining desirable crop yields in Cannabis production, but herein lies the complexity of producing healthy medicinal Cannabis plants in mass quantity.…”
mentioning
confidence: 99%